2022
DOI: 10.3390/plants11070950
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Total Phenolic, Total Flavonoid Contents, and Free Radicals’ Scavenging Potential of Onion Varieties Planted under Diverse Environmental Conditions

Abstract: Genetic diversity and Agro-climatic conditions contribute significantly to the agronomic and morphological features of the food plant species, and their nutraceutical potential. The present study was intended to evaluate the impact of growing conditions on total phenolic and total flavonoid contents, and in vitro antioxidant potential in the bulbs and leaves of onion varieties planted under diverse environmental conditions. Standard analytical methods were used to quantify total phenolic content (TPC), total f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 113 publications
1
16
0
1
Order By: Relevance
“…The Pearson's correlation coefficients also revealed that TPC and TFC were significantly correlated with the ABTS and DPPH radical scavenging capacities. Similar to our results, many studies have consistently reported a correlation between antioxidant activity estimated by ABTS and DPPH assays and the TPC and TFC values [ 23 , 26 , 28 , 29 ]. This suggests that ZO, with the highest TPC and TFC values, could be the main contributor to the antioxidant function of Trikatuk.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Pearson's correlation coefficients also revealed that TPC and TFC were significantly correlated with the ABTS and DPPH radical scavenging capacities. Similar to our results, many studies have consistently reported a correlation between antioxidant activity estimated by ABTS and DPPH assays and the TPC and TFC values [ 23 , 26 , 28 , 29 ]. This suggests that ZO, with the highest TPC and TFC values, could be the main contributor to the antioxidant function of Trikatuk.…”
Section: Discussionsupporting
confidence: 92%
“…The antioxidant capacity was evaluated by the ABTS and DPPH assays which are simple, rapid, inexpensive, acceptable, and widely used [ 21 , 26 ]. DPPH is the free radical most commonly used in antioxidant screening assays where the capacity of each extract could be classified as very strong (IC 50 < 50 μg/mL), strong (IC 50 50–100 μg/mL), moderate (IC 50 101–150 μg/mL), and weak (IC 50 > 150 μg/mL) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…With relevance to the abovementioned facts, the results of the present study demonstrated the increased production of bioactive compounds like TPC and TFC under MS75 and SS50 due to water deficit conditions. These are the secondary metabolites that assist the plant to maintain the osmotic balance and thus cope with water stress scenarios (Mashkor and Muhson, 2014;Bibi et al, 2022;Rahimi et al, 2022). Hence, the foliar supplementation of FA presented non-significant results of TPC and TFC at all levels of irrigation regimes (Figure 10).…”
Section: Discussionmentioning
confidence: 98%
“…Studies have revealed that extracts prepared from the same plant species but collected at different times of the year and/or different locations can present significant differences in their chemical profiles, which in turn affects biological activity (Bibi et al, 2022;Reyes-Vaquero et al, 2021;Shi et al, 2022). The could be due to the presence of defensive compounds targeting these enzymes in insects (Ryan & Byrne, 1988).…”
Section: Ta B L Ementioning
confidence: 99%